2011
DOI: 10.1073/pnas.1103471108
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in mitochondrial histidyl tRNA synthetase HARS2 cause ovarian dysgenesis and sensorineural hearing loss of Perrault syndrome

Abstract: Perrault syndrome is a genetically heterogeneous recessive disorder characterized by ovarian dysgenesis and sensorineural hearing loss. In a nonconsanguineous family with five affected siblings, linkage analysis and genomic sequencing revealed the genetic basis of Perrault syndrome to be compound heterozygosity for mutations in the mitochondrial histidyl tRNA synthetase HARS2 at two highly conserved amino acids, L200V and V368L. The nucleotide substitution creating HARS2 p.L200V also created an alternate splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
202
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(207 citation statements)
references
References 46 publications
3
202
1
1
Order By: Relevance
“…In some cases, overlapping clinical features have been observed from mutations in different genes. For instance, mutations in HARS2 and LARS2 are both associated with sensorineural hearing loss and progressive ovarian failure (OMIM 614926) (Pierce et al 2011;Pierce et al 2013). However, in other cases, different mutations in the same gene result in distinct phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, overlapping clinical features have been observed from mutations in different genes. For instance, mutations in HARS2 and LARS2 are both associated with sensorineural hearing loss and progressive ovarian failure (OMIM 614926) (Pierce et al 2011;Pierce et al 2013). However, in other cases, different mutations in the same gene result in distinct phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Although HSD17B4, mitochondrial histidyl tRNA synthetase (HARS2) and EIF2B should be examined in other cases, it may be time to classify PS type II under the leukodystrophies. The report of Pierce et al (8), represents a valuable contribution, because recent findings in genetic research have suggested that a large number of genetic disorders are highly related in the genotypical root. For example; Alstrom syndrome has begun to be classsified as a ciliopathy (10).…”
Section: Dear Editormentioning
confidence: 99%
“…Long term follow up is very important, since some clinical manifestations appear later in life. Pierce et al (8) evaluated the sisters MK and LK, whose clinical manifestations had been thoroughly described previously by Fiumara et al (13) and Mc Carthy and Opitz (14). Therefore, these sisters are the only cases who have such a detailed clinical history, multidiciplinary approach and long term follow up.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The NGS technology has been used to discover many novel genes that cause mitochondrial related disorders on research bases [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It is now time to bring this technology to clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%